2019
DOI: 10.1590/1808-1657000982018
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of chitin and chitosan from shrimp waste with microwave technique and versatile application

Abstract: In this study, chitin and chitosan were extracted from Litopenaeus vannamei waste using chemical and microwave methods. Shrimp waste was cleaned, dried and ground sieved to 16, 32 and 60 mesh, and the samples were depigmented, demineralized, and deproteinized. Then, the chitin was submitted to a deacetylation process by 45% NaOH solution under microwave irradiation at 600w, for intermittent 15 min or using 5 pulses of 5 minutes. The study showed that the effectiveness of the particle size of 32 mesh and 6 puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
(26 reference statements)
1
8
1
Order By: Relevance
“…Chemical and microwave approaches were used to obtain chitin and chitosan from Pacific whiteleg shrimp, Litopenaeusvannamei garbage. The study found that a particle size of 32 mesh and six 5-min pulses were successful in deacetylation with a degree of 92 percent and a chitosan yield of 52.2 percent [102][103][104]. According to Elieh-Ali-Komi et al [69], the exoskeleton of crustaceans posses varying degrees of chitin, protein, calcium carbonate, phosphate, lipid and ash; however, the proportion of these parameters differ with species (Table 1).…”
Section: Preparation Of Chitin and Its Subsequent Conversion To Chitosanmentioning
confidence: 99%
“…Chemical and microwave approaches were used to obtain chitin and chitosan from Pacific whiteleg shrimp, Litopenaeusvannamei garbage. The study found that a particle size of 32 mesh and six 5-min pulses were successful in deacetylation with a degree of 92 percent and a chitosan yield of 52.2 percent [102][103][104]. According to Elieh-Ali-Komi et al [69], the exoskeleton of crustaceans posses varying degrees of chitin, protein, calcium carbonate, phosphate, lipid and ash; however, the proportion of these parameters differ with species (Table 1).…”
Section: Preparation Of Chitin and Its Subsequent Conversion To Chitosanmentioning
confidence: 99%
“…It is noteworthy that all these steps are directly related to the physicochemical properties of the chitin obtained [ 44 , 45 ]. The source for chitin extraction is subjected to washing, drying, and grinding of powder particles [ 46 ].…”
Section: Chitin Isolation From Natural Resourcesmentioning
confidence: 99%
“…It is noteworthy that all these steps are directly related to the physicochemical properties of the chitin obtained [44,45]. The source for chitin extraction is subjected to washing, drying, and grinding of powder particles [46]. This type of conventional extraction can cause problems in the disposal of waste generated, which is necessary for the neutralization and detoxification of wastewater [47].…”
Section: Chemical Extractionmentioning
confidence: 99%
“…These organisms produce about 100 billion tons of chitin each year [ 89 ]. The chemical structure of chitin, reported in Figure 5 , is different from that of other sugars, since it is characterized by the presence of nitrogen [ 90 ]. It appears as a yellowish powder, with a high molecular weight, insoluble in water and organic solvents, composed of N-acetyl-2-amino-2-deoxy-D-glucose units joined together by glycosidic bonds β, forming a linear chain with some of the deacetylated monomer units ( Figure 5 ) [ 91 , 92 ].…”
Section: Chitin and Chitosanmentioning
confidence: 99%